Independent Continuing Medical Education (CME)/Continuing Professional Development (CPD) Must Deliver Unbiased Information - Margarita Guenova; Robert Schäfer; Paolo Palange (Journal of European CME, 2019)
Physicians commit themselves always to act in the best interests of their patients, and this includes their approach to continuing medical education (CME) as well as continuing professional development (CPD). For many years professional codes, and in some countries also the civil law, have defined that CME/CPD must be independent of commercial interests. Over the last few decades, numerous bodies have introduced CME/CPD accreditation to ensure that the planning and conduct of CME/CPD follows a set of defined standards, with independence of commercial interests as one of the leading principles. Recently industry has proposed that it be accepted by accrediting bodies as a direct provider of accredited CME-CPD. Such a move would not only open the door to the introduction of an inevitable bias in CME/CPD but would jeopardise the professional standing of physicians. Accreditation of CME/CPD currently serves several different purposes, but its credibility depends on whether it can retain its ability to differentiate independent CME/CPD from the provision of commercially framed information.